The ITU's role in the standardization of the GII. - Morre, B.W.
The ITU has embarked on a standardization program for the global information infrastructure (GII) with the fundamental objective that the GII will be a ?federation of networks? consisting of seamlessly interconnected and interoperable communication networks, information processing equipment, databases, and terminals. This article describes the objectives of the ITU studies and outlines the key results so far achieved in the areas of framework architectures and scenarios
Keywords: GII; ITU; Databases; Framework architectures; Global information infrastructure; Information processing equipment; Interconnected communication networks; Interoperable communication networks; Standardization; Terminals